Knowledge, attitude, and willingness towards cadaveric organ donation among Jimma University medical centre health care professionals - Asfaw Gerbi; Mekdes Bekele; Solomon Tesfaye; Getachew Chane; Yohannes Markos (Elsevier, 2020)
Background: Organ donation and transplant rates vary widely across the globe, but there remains an almost universal shortage of deceased donors. The success of clinical transplantation as a therapy for end-stage organ failure is limited by the availability of suitable organs for transplant. Objective: To assess knowledge, attitude, and willingness of Jimma university medical centre (JUMC) health care professionals towards cadaveric organ donation (COD). Method: Institution based cross-sectional study was conducted among 296 health care professionals in JUMC. Data were collected from March to June 2018. A structured and pre-tested questionnaire was used to collect data. Data analysis was done by SPSS version 20.0. Result: Result: Out of 296 healthcare professionals 153 (51.7%) were males and 143 (48.3%) were females. Their mean age was 28.03 ± 4.56 years. The proportion of the participants who had adequate knowledge about COD was 233 (78.7%). More than half of the respondents (54.1%) know the shortage status donated organs for patients with end stage organ failure in the country.About 164 (55.4%) of the professionals had good attitude towards COD; of these, only 40 (13.5%) showed strong agreement. The willingness to donate COD among the participants of the study was found to be 117 (39.5%). Conclusion: Majority of health care professionals in JUMC were well aware of COD. But, their attitude and willingness to BD is highly lower than their knowledge. Hence, intensive education is required to up raise their attitude and willingness in order to develop COD program in the country. Keywords: Cadaveric organ donation, Knowledge, Attitude, Willingness, JUMC